Hypotrichotic nevus in a child with autoimmune family history. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Congenital triangular alopecia is a patch apparently devoid of hair, often localized in the anterior parietal region, with the shape of an isosceles triangle with posterior vertex. It is present since birth or later detectable and anyway stable over time. Precociousness and stability over time make one think of a nevus condition. Its less known name is really Brauer’s nevus (1) or the more explicative term of hypotrichotic nevus. It has been shown that the apparently alopecic area of congenital triangular alopecia actually has a normal density of hair, although being thinner and therefore hypopigmented. The differential diagnosis from alopecia areata is based on clinical - invariability of the alopecia patch over time - and dermoscopic criteria (2) - lack of trichoscopic findings of alopecia areata, such as exclamation mark hairs, pseudocomedones and cadaverized hairs -.